Noise in Telecommunication: Different Types and Methods of dealing with Noise - Akramjon Mirzaev; Sanjar Zoteev (Journal La Multiapp, 2020)
This article discusses noise in telecommunications: different types and methods of dealing with noise. Noise is arguably a very hated problem because it can interfere with the quality of signal reception and also the reproduction of the signal that will be transmitted. Not only that, but noise can also limit the range of the system to a certain emission power and can affect the sensitivity and sensitivity of the reception signal. Even in some cases, noise can also result in a reduction in the bandwidth of a system. Of course, we've all felt how annoying the noise effect is. For example, when listening to the radio, a hissing sound appears on the loudspeaker due to noise. To overcome noise, it is divided into passive noise control and active noise control. Passive noise control is an effort to overcome noise using components that do not require power. Generally passive noise control uses soundproof materials that act as insulation against noise. The method most commonly used to overcome noise is through increasing the gain. The noise is generally in a specific sound area. Hiss is on high frequencies, while noise and hum are on low frequencies. This is the principle underlying the noise reduction method.